Winogrand color - Winogrand, Garry 1928-1984; Almereyda, Michael 1960-; Almereyda, Michael 1960-; Kismaric, Susan (Twin Palms Publishers, 2024)
Garry Winogrand is known primarily for his spontaneous and energetic street photography in black-and-white. What is lesser known is that Winogrand also shot more than 45,000 color slides between the early 1950s and late 1960s. These photographs were often taken between assignments, when the photographer, working on his own, developed and refined an approach to his medium that was increasingly open, independent, and radical. He routinely photographed with two cameras strapped around his neck, one loaded with color film, the other with black and white. Winogrand Color presents 150 photographs selected from the archives at the Center for Creative Photography by the American film director, Michael Almereyda and former Museum of Modern Art curator, Susan Kismaric. It is the first monograph dedicated to the artist's rarely seen color work
Impressum: This second edition of "Winogrand Color" is limited to 5000 casebound copies
Keywords: Winogrand, Garry -- 1928-1984; Geschichte 1951-1967; Mensch -- Motiv; USA -- Motiv; Farbfotografie; Bildband